Trend in Coffee Production and Consumption in Colombia (2017)
Identifying trends in coffee production was the object of this study that analyzed coffee statistics at global and national level considering reports of the International Coffee Organization (ICO), the Agricultural Information System, and Federación Nacional de Cafeteros de Colombia (the latter is the association of Colombian coffee growers).  Factors related to climate variability, increasing of production price, shortages of workforce and volatility of coffee prices, affected the coffee industry and could be structural causes of declining production trends found in some producing countries as well as some departments that traditionally are coffee growers in Colombia.